Composites of rigid polyurethane foams and silica powder filler enhanced with ionic liquid. (May 2019) - Członka, Sylwia; Strąkowska, Anna; Strzelec, Krzysztof; Kairytė, Agnė; Vaitkus, Saulius
Abstract: Rigid polyurethane foams (RPUFs) were successfully modified with different weight ratios (0.5 wt%, 1 wt%, 2 wt%) of nanosilica and nanosilica suspension (nanosilica-enhanced with ionic liquid, 1-butyl-3-methylimidazolium hexafluorophosphate, [bmim][PF6 ]). The resulting foams were evaluated by their processing parameters, chemical structure (Fourier Transform Infrared Spectroscopy Analysis, FTIR), morphology (Scanning Electron Microscopy Analysis, SEM), mechanical properties (compressive test, three-point bending test), viscoelastic behavior (Dynamic Mechanical Analysis, DMA), thermal property (Thermogravimetric Analysis, TGA, thermal conductivity) and application properties (water absorption, dimensional stability). The results showed that the morphology of modified foams is significantly affected by the type of the filler and filler content, which resulted in inhomogeneous, irregular, large cell shapes and further affected the physical and mechanical properties of resulting materials. RPUFs modified with nanosilica suspension represent better mechanical and thermal properties comparing to the RPUFs modified with pure nanosilica. The results showed that the best results were obtained for RPUFs modified with 1 wt% of nanosilica suspension. In comparison with unfilled foam, compositions modified with 1 wt% of nanosilica suspension provide higher density (44 kg/m 3 ), greater compression strength (258 kPa measured parallel and 162 kPa measured perpendicular), and lower thermal conductivity (0.026 W/m·K). The results obtained in this study suggest that the introduction of nanosilica and nanosilica suspension over a certain optimal level (such as 2 wt%) has a negative effect on the cell morphology, which leads to deterioration of physico-mechanical properties of the modified foams. Highlights: Nanosilica (NS) and nanosilica enhanced with ionic liquid (NS suspension) have influence on foaming process of PU system . Morphology of RPUFs is significantly affected by the fillers content . RPUFs containing 0.5 and 1 wt% of NS and NS suspension are characterized by better mechanical and thermal properties . Introduction of NS and NS suspension over a certain optimal level (2 wt%) leads to deterioration of physico-mechanical properties of the RPUFs .